2013
DOI: 10.1037/a0029449
|View full text |Cite
|
Sign up to set email alerts
|

The SRP-II as a rich source of data on the psychopathic personality.

Abstract: This study examines the factor structure, external correlates, and predictive utility of the Self-Report Psychopathy scale (SRP-II;Hare, Harpur, & Hemphill, 1989). It was hypothesized that the SRP-II would sufficiently tap facets of the psychopathic personality, despite failing to replicate the structure of the PCL-R, and thereby provide a rich source of data for examining the construct of psychopathy as delineated by Cleckley (1941). Participants for the current investigation were 1257 undergraduate students … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 62 publications
0
30
0
Order By: Relevance
“…The factor structure of the SRP-II was previously examined with the sample used in the current study (Lester et al, 2013); neither Hare et al’s (1989) original two-factor model nor Benning, Patrick, Salekin, and Leistico (2005); 23-item two-factor model was found to achieve adequate fit in this sample. Thus, Lester et al’s (2013) rationally derived 36-item four-factor model was used to test against a unidimensional SRP-II model. Across all four self-report measures, the factor models showed better fit than the unidimensional model; model fit indices are presented in supplementary material Appendix 1, Table 1.…”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…The factor structure of the SRP-II was previously examined with the sample used in the current study (Lester et al, 2013); neither Hare et al’s (1989) original two-factor model nor Benning, Patrick, Salekin, and Leistico (2005); 23-item two-factor model was found to achieve adequate fit in this sample. Thus, Lester et al’s (2013) rationally derived 36-item four-factor model was used to test against a unidimensional SRP-II model. Across all four self-report measures, the factor models showed better fit than the unidimensional model; model fit indices are presented in supplementary material Appendix 1, Table 1.…”
Section: Resultsmentioning
confidence: 72%
“…A rationally derived 36-item four-factor model (Lester et al, 2013) was adopted in this study. The four factors are interpersonal (IP = 16 items), disinhibition/impulsivity (DI = nine items), fearlessness (F = five items), and coldheartedness (C = six items).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, it is also possible to find other reduced versions such as the 34 items developed by Mahmut, Menictas, Stevenson, and Homewood (2011) and the 28 items developed by Carré, Hyde, Neumann, Viding, and Hariri (2012). These different versions of the SRP have shown good internal consistency (ranging from α = .69 to α = .90) and construct validity (Lester, Salekin, & Sellbom, 2013;Williams, Paulhus, & Hare, 2007).…”
mentioning
confidence: 99%
“…Earlier versions have been found to have validity as self-report measures of psychopathy. For example, the four factors of the SRP-II being significant predictors of external correlates relevant to psychopathy in a student population (Lester, Salekin, & Sellbom, 2013). Research with college students and community samples have found the Hare SRP scale to have good convergent and discriminate validity and a factor structure reflecting that of the PCL-R (Mahmut, Menictas, Stevenson, & Homewood, 2011;Neal & Sellbom, 2012).…”
Section: Hare Self-report Psychopathy Scalementioning
confidence: 98%